Seni Lingkungan (Environmental Art) dalam Seni Rupa Kontemporer Studi Kasus: Pameran Biennale Jakarta Tahun 2015 - Ramli, Zaenudin; Roos Nagara, Martien (PANGGUNG, 2025)
This study analyzes the representation of environmental art in the context of Indonesian contemporary art, using the Jakarta Biennale 2015 as its main case study. This research addresses the problem of how contemporary artworks in the exhibition reflect a critique of relevant ecological and social issues. The study employs a descriptive-interpretative analysis method of selected artworks, supported by data from the exhibition catalog and related literature. The findings indicate that the environmental artworks in the Jakarta Biennale 2015 not only function as aesthetic expressions but also serve as a powerful medium for social critique and public agitation. This finding contributes to the understanding of the role of contemporary art exhibitions as critical platforms for sustainability discourse in Indonesian art.